Typologies of violence against women in Brazil: A latent class analysis of how violence and HIV intersect. Issue 11 (1st November 2020) - Tsuyuki, Kiyomi; Stockman, Jamila K.; Knauth, Daniela; J. Catabay, Christina; He, Feng; Al-Alusi, Noor A.; Pilecco, Flavia Bulegon; Jain, Sonia; Barbosa, Regina Maria
ABSTRACT: We address the limited understanding around the overlap between violence and HIV in Brazil. Data was from two clinic-based samples of HIV-positive ( n  =   1534) and HIV-negative women ( n  =   1589) in São Paulo and Porto Alegre. We conducted latent class analysis and identified violence typologies by type of violence, life course timing, frequency, and perpetrator, stratified by city and HIV-status. Overall, HIV-positive women experienced more lifetime physical and sexual violence than HIV-negative women. Twelve unique violence latent classes were identified. In São Paulo, HIV-positive women were likely to have endured physical violence several times (Conditional Probability [CP]: 0.80) by an intimate partner (CP: 0.85), and sexual violence several times (CP: 0.46) by an intimate partner (CP: 0.62). In Porto Alegre, HIV-positive women endured physical violence several times (CP: 0.80) by an intimate partner (CP: 0.70) during childhood/adolescence (CP: 0.48), and sexual violence several times (CP: 0.54) by an intimate partner (CP: 0.60). Findings inform interventions to educate around gender equity, violence, and the health effects of violence including HIV, integrate HIV and violence services, and improve the provision of bio-medical HIV prevention among HIV-negative women who experience violence.